Complex inclusive categories of positive and negative valence and prototypicality claims in asymmetric intergroup relations. (27th June 2016) - Alexandre, Joana Dias; Waldzus, Sven; Wenzel, Michael
Abstract : Based on the premise that groups' social standing and regard depend on their prototypicality for superordinate categories, minorities can be understood to suffer from the fact that they are considered as less prototypical than majorities. Previous research has shown that complex (vs. simple) representations of superordinate categories can reduce majority members' tendency to perceive their in‐group as more prototypical than the out‐group. The current research tested whether such complex representations also increase minorities' own perceived relative in‐group prototypicality (RIP), leading to more balanced prototypicality judgments from both majorities and minorities. In Study 1 ( N  =   76), an experiment with two artificial groups of unequal status, a complex representation of a superordinate category increased the comparatively low RIP of the lower status subgroup. Consistently, in Study 2 ( N  =   192), a correlational study with natural groups, the relation between perceived complexity of the superordinate category and RIP was positive for members of the lower status group but negative for members of the higher status comparison group. In Study 3 ( N  =   160), an experiment with natural groups, a more complex representation of the superordinate category led lower and higher status groups to perceive greater equality in terms of relative prototypicality not only for a positive but also for a negatively valued superordinate category. These results have important implications for the understanding of social change: As superordinate identity complexity implies that included subgroups are more equally prototypical, it offers a normative alternative that helps minorities to challenge asymmetric status relations vis‐à‐vis majorities, but also promotes hope that majorities show bipartisanship in supporting such social change.